Lower urinary tract symptoms following discontinuation of long-term non-medical use of testosterone preparations - Kh. S. Ibishev; V. A. Sharbabchiev; A. I. Paleny; M.-Kh. M. Uzhakhov; A. D. Mezhidova (Вестник урологии, 2022)
Introduction. The aging process in men is accompanied by a progressive decrease in the level of serum testosterone (Tc). In addition to chronological aging, various factors contribute to the decline in testosterone levels. One of such factors contributing to the decrease in endogenous Tc and the development of secondary hypogonadism is the long-term use of testosterone preparations (TPs) used for non-medical purposes.Objective. To assess the nature of lower urinary tract symptoms following discontinuation of long-term non-medical use of testosterone preparations.Materials and methods. A clinical and statistical analysis of examination results in 31 men aged 22 – 46 years who received TPs for non-medical purposes while visiting gyms and subsequently turned to urologist with complaints of lower urinary tract symptoms (LUTS) was carried out. The study used the International Prostatic Symptom Score (IPSS) questionnaire, laboratory and instrumental examinations: general urine examination, general blood examination, prostate secretion microscopy, evaluation of serum total Tc, follicle-stimulating and luteinizing hormones, prolactin, estradiol, prostate ultrasound and bladder ultrasound, uroflowmetryResults. When assessing LUTS, the prevalence of irritative symptoms was noted. The level of serum total Tc in 13 (41.9%) men was in the range of 8 – 11 nmol/l, in 18 (58.1%) men it was below 8 nmol/l. In addition, most patients (77.4%) had areas of reduced blood flow in the prostate, and 67.7% had prostate fibrosis.Conclusion. Discontinuation of the use of long-term non-medical TPs can lead to the development of secondary hypogonadism and LUTS, which in most cases are irritative. In the treatment of these patients, an interdisciplinary rehabilitation program should be developed.